Impact of advanced lung cancer inflammation index on all-cause mortality among patients with heart failure: a systematic review and meta-analysis with reconstructed time-to-event data - Ahmed Mazen Amin; Ramy Ghaly; Hossam Elbenawi; Abdelrahman Ewis; Ubaid Khan; Khaled S. M. Elshaer; Mohamed Abuelazm; Basel Abdelazeem; Brijesh Patel; Farris K. Timimi; Islam Y. Elgendy (Cardio-Oncology)
Abstract Background Heart failure (HF) is associated with systemic inflammation and hypercatabolic syndrome, impacting body metabolism. The advanced lung cancer inflammation index (ALI) is a novel inflammatory and nutritional biomarker. We aimed to investigate the prognostic role of ALI in patients with HF. Methods We comprehensively searched PubMed, WOS, SCOPUS, EMBASE, and CENTRAL through October 2024. We conducted a pair-wise and prognostic systematic review and meta-analysis with a reconstructed time-to-event data meta-analysis. All analyses were performed using R V. 4.3.1. This meta-analysis was registered at PROSPERO (CRD42024535227). Results We included five studies with 2,795 patients. In the pair-wise meta-analysis, ALI ≤ 25 was significantly associated with an increased incidence of all-cause mortality compared with ALI > 25 (risk ratio [RR] 1.73, 95% confidence interval [CI] 1.36–2.21, P < 0.01). On the adjusted prognostic meta-analysis, higher ALI was significantly associated with a reduction in the risk of all-cause mortality (hazards ratio [HR] 0.45, 95% CI 0.35–0.58-, P < 0.01). The reconstructed Kaplan Meier showed that ALI > 25 was significantly associated with a 56% reduction in the risk of all-cause mortality compared with ALI ≤ 25 (HR 0.44, 95% CI 0.38–0.50, P < 0.000001). Conclusion Among patients with HF, a low ALI was associated with a higher incidence of all-cause mortality rate than those with a high ALI. These findings suggest that ALI can be used for prognostic stratification and aid clinical decision-making in HF management.